KEMUNGKINAN PEMANFAATAN BEBERAPA JENIS BAMBU TERTENTU, BERDASARKAN POLA PENYUSUNAN BERKAS PEMBULUH, SEBAGAI BAHAN BAKU PULP DAN KERTAS - Nani Nuriyatin; Kurnia Sofyan (BRIN Publishing, 2011)
The abundant availability of bamboos in Indonesia bas prompted their possible uses as raw material for pulp and paper. This is expected to replace its corresponding conventional raw materials (i.e. woods), which nowadays tend to be dwindling, scarce, and limited. In relevant, this research aims to assess the suitability of bamboo stem for such comprision several species. The grouping of bamboo species brought out the results,i.e. Arundinaria hundsii and Arundinaria javonica as pattern 1; Cephalostachyum pergracile and Melocanna baccifera as pattern 2; Dendrocalamus strictus and Dendrocalamus giganteus as pattern 3; and Dendrocalamus asper and Gigantochloa apus as patterns 3 and 4). In assessing the bamboo suitability for pulp and paper, an approach was taken whereby the bamboo species in the particular pattern was examined of fiber dimensions (i.e. fiber length, fiber flexibility, rigidity coefficient, Runkel ratio, and Mubistep ratio). To evaluate whether there were significant differences in the examination/ determination results among those 4 patterns, the analysis of variances (probability levels) with completely standardized one-factor design was employed followed with the different range test of the resulting means (Le. Tuckey procedures). The factor was those four bamboo patterns. Results revealed that each of those four patterns based on fiber length and felting power belonged to class I, indicating as the most favourable for pulp and paper. Meanwhile, other scrutiny based on fiber flexibility, rifidity coefficient, Runkel ratio, and Mublstep ratio turnd out that all the patterns belonged to class M. Further, bamboo species catagoried as pattern I exchibited species characters such as affording the bigbest fiber flessibility and lowest rigidity coefficient as well as runkel ratio compared to those of the alber patterns. Meanwhile, bamboo species in pattern 4 exhibited the bigbest fiber length and felting power. Ultimately, assessment on the overall fiber dimensions and their derived values came about that all the four bamboo pattern belonged to class III, as indicative qualities of the resulting pulp and paper However, to make sure whether such indication proved true, further in-depth research on the pulp and paper processing from those entire bamboos (pattern 1 until 4) deserves carrying out.